Association of changes in lifestyle with changes in sleep difficulties: an analysis of 38 400 participants over a 16-year follow-up - Saltychev Mikhail; Juhola Juhani; Ervasti Jenni; Kivimäki Mika; Pentti Jaana; Myllyntausta Saana; Vahtera Jussi (BMJ PUBLISHING GROUP, 2022)
Objectives To investigate the association between changes in lifestyle risk factors and changes is sleep difficulties.
Design Longitudinal repeated measures cohort study.
Setting University and national institute of occupational health.
Participants Participants of the Finnish Public Sector study with information on sleep and lifestyle-related risk factors collected in five repeat surveys with 4-year intervals from 2000 to 2017. The participants were those, who had responded at least twice and had a change in sleep difficulties (having sleep difficulties vs not) (142 969 observations from 38 400 respondents (mean age 45.5 (SD 9.2) years, 83% women).
Primary and secondary outcome measures Changes in sleep quality over time. Longitudinal fixed effects analysis, a method that accounts for time-invariant confounders by design, was used.
Results At first available response, sleep difficulties were experienced by 13 998 (36%) of the respondents. Respectively, the mean age was 44.3 (10.0) years, 7526 (20%) were obese, 13 487 (35%) reported low physical activity, 3338 (9%) extensively drinking and 6547 (17%) were smoking. Except for smoking, the changes in the studied modifiable risks were associated with changes in sleep difficulties. The ORs for having sleep difficulties were 1.41 (95% CI 1.35 to 1.48) for obesity, 1.10 (95% CI 1.06 to 1.13) for low physical activity and 1.43 (95% CI 1.35 to 1.51) for heavy drinking. For smoking, the association was negative with OR 0.81 (95% CI 0.76 to 0.86). Including all four modifiable risks into model changed the estimates only little.
Conclusions The results of this longitudinal study suggest that changes in sleep quality are interconnected with changes in lifestyle.